2021
DOI: 10.21203/rs.3.rs-166550/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Soil and Microbial Characteristics and Microbial Response in Rare Earth Mining Areas in Jiangxi Province, China.

Abstract: There is a certain connection between the microbial community and functional flora in rare earth mining areas, but the pollution characteristics and pollution metabolic pathways in the mining area are still unclear. The conditions of heavy metals, rare earth elements, and microorganisms after the mining of rare earth mines were studied in this paper. It was found that after mining, all the sampling areas showed low pH and low total organic carbon(TOC), accompanied by high iron and aluminum concentrations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In addition to ammonium salts, rare earth workers have also studied the effects of magnesium and calcium salts on the seepage process. Liang et al [18] found that magnesium sulfate and calcium chloride, as leaching solutions, can strongly compress the double layer of weathered crust elution-deposited rare earth ore particles after entering the ore body. This helps to prevent the migration of fine particles during leaching, decrease the likelihood of pore blockage, and enhance the permeability of the ore body.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ammonium salts, rare earth workers have also studied the effects of magnesium and calcium salts on the seepage process. Liang et al [18] found that magnesium sulfate and calcium chloride, as leaching solutions, can strongly compress the double layer of weathered crust elution-deposited rare earth ore particles after entering the ore body. This helps to prevent the migration of fine particles during leaching, decrease the likelihood of pore blockage, and enhance the permeability of the ore body.…”
Section: Introductionmentioning
confidence: 99%